(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cisplatin-paclitaxel is a combination of chemotherapy drugs used in the treatment of head and neck malignancy. The main side effect of cisplatin is nephrotoxicity. Nephrotoxicity manifests in decreased glomerular filtration rate (GFR), increased blood urea nitrogen (BUN) and creatinine serum, and decreased magnesium and potassium serum. Objective: this study aimed to determine the nephrotoxicity effects of post cisplatin-paclitaxel chemotherapy in patients with malignant head and neck tumors. Method: Patients with malignant head and neck tumor who received cisplatin-paclitaxel chemotherapy were taken consecutively and examined their GFR, BUN, creatinine, magnesium and potassium pre- and post-chemotherapy. The data were statistically analyzed whether nephrotoxicity happened post cisplatinpaclitaxel chemotherapy. Result: Thirty five samples consisted of 24 men and 11 women. The diagnose were 25 nasopharyngeal carcinoma (71.42%), 3 of each sinonasal carcinoma and laryngeal carcinoma (8.57%), and 1 of each tongue carcinoma, parotid carcinoma, tonsillar carcinoma and MAE carcinoma (2.86%). The average of prechemotherapy GFR was 94.43±17.44 ml/min, average of post-chemotherapy GFR was 68.17±17.96. Mostly found decreased mild kidney function in 24 (68.57%) post chemotherapy patients. Conclusion: There was a nephrotoxicity effects after cisplatin-paclitaxel chemotherapy treatment in patients with head and neck malignant tumors treated